The - edited by Michael J. Loux; Dean W. Zimmerman (Oxford University Press, 2003)
The Oxford Handbook of Metaphysics offers the most authoritative and compelling guide to this diverse and fertile field of philosophy. Twenty-four of the world's most distinguished specialists provide brand-new essays about 'what there is': what kinds of things there are, and what relations hold among entities falling under various categories. They give the latest word on such topics as identity, modality, time, causation, persons and minds, freedom, and vagueness. The Handbook's unrivaled breadth and depth make it the definitive reference work for students and academics across the philosophical spectrum